Systemic Gene Expression in Arabidopsis during an Incompatible Interaction with Alternaria brassicicola - Schenk, Peer M. (The American Society for Plant Biologists, 2003)
Pathogen challenge can trigger an integrated set of signal transduction pathways, which ultimately leads to a state of “high alert,” otherwise known as systemic or induced resistance in tissue remote to the initial infection. Although large-scale gene expression during systemic acquired resistance, which is induced by salicylic acid or necrotizing pathogens has been previously reported using a bacterial pathogen, the nature of systemic defense responses triggered by an incompatible necrotrophic fungal pathogen is not known. We examined transcriptional changes that occur during systemic defense responses in Arabidopsis plants inoculated with the incompatible fungal pathogen Alternaria brassicicola. Substantial changes (2.00-fold and statistically significant) were demonstrated in distal tissue of inoculated plants for 35 genes (25 up-regulated and 10 down-regulated), and expression of a selected subset of systemically expressed genes was confirmed using real-time quantitative polymerase chain reaction. Genes with altered expression in distal tissue included those with putative functions in cellular housekeeping, indicating that plants modify these vital processes to facilitate a coordinated response to pathogen attack. Transcriptional up-regulation of genes encoding enzymes functioning in the β-oxidation pathway of fatty acids was particularly interesting. Transcriptional up-regulation was also observed for genes involved in cell wall synthesis and modification and genes putatively involved in signal transduction. The results of this study, therefore, confirm the notion that distal tissue of a pathogen-challenged plant has a heightened preparedness for subsequent pathogen attacks.